Last Glacial Maximum cirque glaciation in Ireland and implications for reconstructions of the Irish Ice Sheet. (1st June 2016) - Barth, Aaron M.; Clark, Peter U.; Clark, Jorie; McCabe, A. Marshall; Caffee, Marc
Abstract: Reconstructions of the extent and height of the Irish Ice Sheet (IIS) during the Last Glacial Maximum (LGM, ∼19–26 ka) are widely debated, in large part due to limited age constraints on former ice margins and due to uncertainties in the origin of the trimlines. A key area is southwestern Ireland, where various LGM reconstructions range from complete coverage by a contiguous IIS that extends to the continental shelf edge to a separate, more restricted southern-sourced Kerry-Cork Ice Cap (KCIC). We present new 10 Be surface exposure ages from two moraines in a cirque basin in the Macgillycuddy's Reeks that provide a unique and unequivocal constraint on ice thickness for this region. Nine 10 Be ages from an outer moraine yield a mean age of 24.5 ± 1.4 ka while six ages from an inner moraine yield a mean age of 20.4 ± 1.2 ka. These ages show that the northern flanks of the Macgillycuddy's Reeks were not covered by the IIS or a KCIC since at least 24.5 ± 1.4 ka. If there was more extensive ice coverage over the Macgillycuddy's Reeks during the LGM, it occurred prior to our oldest ages. Highlights: New 10 Be surface exposure dates from a cirque basin in southwestern Ireland. Alpine glaciation existed during the LGM. Results suggest a more restricted LGM Irish Ice Sheet. Direct implications for future reconstructions of the Irish Ice Sheet.